EKSPLORASI NILAI PENDIDIKAN KARAKTER DALAM TRADISI REWANG SEBAGAI BAHAN AJAR IPAS DI SD - Riska, Nora; M. Jaya Adiputra; Erlisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the values ​​of character education in the rewang tradition and integrate them as teaching materials in science (natural and social sciences) subjects at the elementary school (SD) level. The rewang tradition, which is an activity of community cooperation in helping organize certain events such as weddings, reflects various positive values. The research methodology used is qualitative ethnography which refers to direct observation and awareness of the culture and social systems of certain groups or communities to provide descriptive explanations and interpretations. The study was conducted in June-August 2024 in Muara Bahan Village. The data sources used are primary data sources and secondary data sources. The data collection instruments used are observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and verification, after data collection and recording. The results of the study show that there are three character values ​​in the rewang tradition, the first is the value of faith and devotion to God Almighty and noble character, the second is the value of mutual cooperation and the third is the value of global diversity. These three values ​​can be used as teaching materials for science in Chapter 6 "My Indonesia is Rich in Culture, in Topic A Uniqueness of the Habits of the People Around Me".